A sexualidade de mulheres vivendo com AIDS: contribuições da psicanálise - FLEXA, Jucélia Pereira (Universidade Federal do Pará, 2014)
The feminization of HIV/aids is a reality in Brazil, according to the Health Ministry's epidemiological data. This work is based on the psychoanalysis referential and presents the case study of Larissa, outpatient at the ambulatory for Specialized Assistance in HIV/aids of the University Hospital João de Barros Barreto. The starting point was the hypothesis that women living with HIV/aids may present subjective consequences before a traumatic diagnosis associated with taboos such as death and sexuality. For Larissa having aids meant rejection, discrimination and abandonment by her partner and parents. On her visits she expressed her concern with how to tell her boyfriend about the virus, fearing an aggressive reaction, talked about her childhood and an adolescence of conflicts with her parents, her father's aggression and complained about her mother, mainly for her not having said anything related to sexuality. In her romantic relationships with men and problems with the law, one might think, according to psychoanalytic theory, that her helplessness may have lead her to masochism. Larissa's ideal of love with these partners points to aspects of a romantic love, in which she expected to find protection and trust. Furthermore, this research also highlights the presence of uneasiness between mothers and daughters realted to talks pertaining to sexuality, the body and female desire, that is, the absence of sexual education which in Larissa's case, left her at the mercy of her partners, without resources to protect herself from diseases such as aids and teenage pregnancy. Larissa's account is in line with those of other female patients living with HIV, investigated in this research, and can serve as a warning to the problem presented on the Brazilian Epidemiological Bulletin of 2012's data, where the incidence of cases of HIV infection in young people from 13 to 19 years is increasing, women being the majority. For Larissa, being able to talk about her sexuality at the clinic, allowed her to find the meanings of the traumatic aspects experienced in her childhood and adolescence, to face her internal conflicts and her sense of helplessness, to think about her relationship with her mother and her daughters and, finally, to say she was "learning to be a woman", which, for her, meant being "more prepared" for life.